Empowering MSMEs in The Digital Era: A Systematic Literature Review on The Role of Digital Literacy - Hermansyah Hermansyah; Usep Suhud; Mohammad Rizan (Greenation International Journal of Economics and Accounting, 2025)
Introduction/Main Objectives: This study regularly examines the role of digital literacy in empowering MSMEs by exploring its impact on business performance, innovation, and sustainability. Background Problems: State the problem or economic/business phenomena studied in this paper and specify the research question(s) in one sentence. Novelty: Using a systematic literature review approach, this research identifies key challenges and opportunities MSMEs face in adopting digital technologies. Research Methods: Micro, Small, and Medium Enterprises (MSMEs) play a vital role in fostering economic growth at both global and local levels. In many countries, MSMEs significantly contribute to job creation, Gross Domestic Product (GDP) growth, and poverty reduction. However, despite their significant contributions, MSMEs often need help with structural and operational challenges that hinder their growth and competitiveness, particularly in the increasingly competitive digital era.  Finding/Results: Digital transformation offers substantial opportunities for MSMEs to enhance their operational efficiency, access broader markets, and increase productivity. Nevertheless, one of the primary obstacles to adopting digital technologies is the low level of digital literacy among MSME actors. Digital literacy, encompassing the ability to understand, use, and effectively leverage digital technologies, is a critical factor in the success of MSMEs in this era. Conclusion: Furthermore, the study highlights the importance of digital literacy training and supportive policies to bridge the digital gap and enhance MSME competitiveness in the digital economy. The findings provide insights and recommendations for policymakers and practitioners to develop strategies that support digital literacy development and empower MSMEs to thrive in the dynamic digital era.